INTERREGIONAL ECONOMIC LINKAGES AND AGRI-FOOD MARKET DEVELOPMENT IN NAMANGAN REGION: CHALLENGES AND STRATEGIC PATHWAYS (European Journal of Interdisciplinary Research and Development, 2025)
This study examines the interregional economic linkages and agri-food market development in Namangan Region, Uzbekistan, focusing on existing challenges and strategic pathways for sustainable growth. The research is motivated by the increasing importance of food security, regional cooperation, and efficient resource allocation in the context of globalization and economic transformation. Drawing on the methodological framework of Input–Output Analysis, supported by statistical, comparative, and econometric techniques, the study evaluates the dynamics of production, trade flows, and market integration across Namangan and neighboring regions. The findings reveal that while Namangan possesses a substantial agri-food production potential, its market efficiency is constrained by structural imbalances, underdeveloped logistics, and limited diversification of interregional trade partners. Natural resource constraints, high demographic pressure, and seasonal price fluctuations further challenge market stability. The study also identifies untapped opportunities in specialized production zones, cluster-based cooperation, and the establishment of modern agri-logistics centers.